THE ROLE OF SOCIAL MEDIA MARKETING ON BRAND AWARENESS AND STUDENT DECISIONS TO CHOOSE UNIVERSITY - Yoga Kharisma, Alfin; Haryono, Tulus (LPPM Universitas Duta Bangsa Surakarta, 2023)
This study is aimed to analyze the influence of social media marketing activities on brand awareness and students' decisions in choosing higher education institutions. The population in this study was students of Universitas Duta Bangsa, data collection methods using online questionnaires, and data analysis methods using SEM-PLS. The results of this study found that marketing activities through social media have a positive effect on the decision to choose a university. The components of social media marketing activities that influence the decision to choose a university are entertainment, interactivity, trendy, customization, and E-WOM. Meanwhile, what affects brand awareness is entertainment, customization, and E-WOM.